2009
DOI: 10.1136/jnnp.2008.151324
|View full text |Cite
|
Sign up to set email alerts
|

Vascular risk factors and morphometric data in cervical artery dissection: a case-control study

Abstract: BACKGROUND: Limited knowledge exists on vascular risk factors, body height and weight in patients with spontaneous cervical artery dissection (sCAD). PATIENTS AND METHODS: In this case-control study, major vascular risk factors, body weight, body height and body mass index (BMI) of 239 patients obtained from a prospective hospital-based sCAD registry were compared with 516 age-and sex-matched healthy controls undergoing systematic health examinations in the Clinical and Preventive Investigations Center, Paris.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 25 publications
2
33
0
5
Order By: Relevance
“…The lower mean BMI and lower prevalence of obesity and overweightness in CEAD patients compared with referents are in agreement with recently published results from an independent French group for 239 patients and 516 referents. 19 The lower prevalence of vascular risk factors in CEAD patients compared with young non-CEAD IS patients is in line with previous publications. 8 -10 Although the association of vascular risk factors with IS risk is well established in older individuals, few data are available in young adults.…”
supporting
confidence: 79%
See 2 more Smart Citations
“…The lower mean BMI and lower prevalence of obesity and overweightness in CEAD patients compared with referents are in agreement with recently published results from an independent French group for 239 patients and 516 referents. 19 The lower prevalence of vascular risk factors in CEAD patients compared with young non-CEAD IS patients is in line with previous publications. 8 -10 Although the association of vascular risk factors with IS risk is well established in older individuals, few data are available in young adults.…”
supporting
confidence: 79%
“…Two studies described an increased prevalence of hypertension in CEAD patients 15,16 (restricted to CEAD patients with cerebral ischemia in 1 study, 16 which partly overlaps with our Italian subsample), whereas 2 other studies reported no association. 17,19 In the present sample, we found a significantly higher frequency of hypertension in CEAD patients compared with referents, regardless of the presence or absence of cerebral ischemia. Although a lower prevalence of hypercholesterolemia has been described in CEAD patients compared with non-CEAD IS patients, 10 to the best of our knowledge, no such association has been reported in comparison with referents.…”
Section: In the Context Of The Current Literaturesupporting
confidence: 55%
See 1 more Smart Citation
“…[1][2][3] Although dissection of the extracranial cervical arteries has been extensively studied and described, [4][5][6][7][8][9][10][11][12] less information is available about pure intracranial artery dissection (ie, not including the cervical portion of the artery). 4 Early reports were exclusively based on autopsy series, hence biased towards the most severe cases of intracranial artery dissection.…”
Section: Introductionmentioning
confidence: 99%
“…Atherosclerosis appears to be rare in patients affected by cervical artery dissection [5]. Several studies investigated the potential link of cervical artery dissection with common risk factors for atherosclerosis [5][6][7]. In the largest study Debette et al [6] reported that hypertension was associated with an increased risk of cervical artery dissection, whereas an inverse association with hypercholesterolemia, obesity and overweight was observed.…”
Section: Discussionmentioning
confidence: 99%